2006
DOI: 10.1161/circulationaha.105.000356
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Atorvastatin Improves Hypercholesterolemic Coronary Endothelial Dysfunction Without Improving the Angiogenic Response

Abstract: Background-Although 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitors (statins) can restore endothelial function in coronary disease, in vitro and murine studies have shown their effects on myocardial angiogenesis to be biphasic and dose dependent. We investigated the functional and molecular effects of high-dose atorvastatin on the endogenous angiogenic response to chronic myocardial ischemia in hypercholesterolemic swine. Methods and Results-Yucatan pigs were fed either a normal (NORM grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 34 publications
2
43
0
Order By: Relevance
“…Our experiments suggested that epithelial cell proliferation and reversal of emphysema were observed dose-dependently within the range of 0 -5 mg⅐kg Ϫ1 ⅐day Ϫ1 of SS. Although decreased plasma VEGF concentrations in the late-phase model may reflect the inhibitory effects of high-dose statins on endothelial functions as previously reported (9,35), BALF VEGF levels tended to increase and emphysematous changes were significantly improved by treatment with the medium dose of SS (1 mg⅐kg Ϫ1 ⅐day Ϫ1 ), as a consequence, in this protocol. Since the low and medium doses of SS (0.2 and 1 mg⅐kg Ϫ1 ⅐day Ϫ1 , respectively) correspond to those in patients with hyperlipidemia, our findings related to its dosedependent favorable effects on emphysema may promise further clinical implication.…”
Section: Discussionsupporting
confidence: 63%
“…Our experiments suggested that epithelial cell proliferation and reversal of emphysema were observed dose-dependently within the range of 0 -5 mg⅐kg Ϫ1 ⅐day Ϫ1 of SS. Although decreased plasma VEGF concentrations in the late-phase model may reflect the inhibitory effects of high-dose statins on endothelial functions as previously reported (9,35), BALF VEGF levels tended to increase and emphysematous changes were significantly improved by treatment with the medium dose of SS (1 mg⅐kg Ϫ1 ⅐day Ϫ1 ), as a consequence, in this protocol. Since the low and medium doses of SS (0.2 and 1 mg⅐kg Ϫ1 ⅐day Ϫ1 , respectively) correspond to those in patients with hyperlipidemia, our findings related to its dosedependent favorable effects on emphysema may promise further clinical implication.…”
Section: Discussionsupporting
confidence: 63%
“…It appears that low doses induce proangiogenic effects through Akt activation, which leads to eNOS phosphorylation and NO production [16]. Boodhwani et al has shown that atorvastatin at higher doses improves coronary endothelial dysfunction in hypercholesterolemic animals without improving angiogenic response [17]. Statins have also been shown to have dose dependent effects on VEGF expression [18].…”
Section: Discussionmentioning
confidence: 99%
“…Statins increase nitric oxide bioavailability through the activation of Akt (71,72,77,78). Akt induces endothelial nitrous oxide synthase production and enhances its activity (71,72,77,78).…”
Section: Lipid-lowering Agentsmentioning
confidence: 99%